An Evaluation of Indonesian National Work Competency Standards (SKKNI): A Case Study of the Gili Balu - Azizurrohman, Muhammad; Habibi, Putrawan; Supiandi, Supiandi (Journal of Indonesian Tourism, Hospitality and Recreation, 2022)
ABSTRACTThe aim of this study is to evaluate the skills possessed by human resources in the Gili Balu area, West Sumbawa. This research is important because in practice the Gili Balu area is under tourism development so it is necessary to evaluate the ability of the surrounding community in the tourism industry. By using descriptive qualitative methods and in-depth interviews with 75 respondents, the authors evaluate several indicators such as the ethics of tourism actors, administrative procedures and understanding of technology, first aid skills, conflict resolution, communication skills, and work experience. The author found that tourism actors at Poto Tano Village, Tambak Sari Village, Kiantar Village, Senayan Village were declared to have not met the Indonesian National Work Competency Standards (SKKNI). ABSTRAKTujuan dari penelitian ini adalah untuk mengevaluasi keterampilan yang dimiliki sumber daya manusia di kawasan Gili Balu, Sumbawa Barat. Penelitian ini penting dilakukan karena dalam pelaksanaannya kawasan Gili Balu sedang dalam pengembangan pariwisata sehingga perlu dilakukan evaluasi terhadap kemampuan masyarakat sekitar dalam industri pariwisata. Penelitian ini menggunakan metode deskriptif kualitatif dan wawancara mendalam kepada 75 responden, penulis menilai beberapa indikator seperti etika pelaku pariwisata, prosedur administrasi dan pemahaman teknologi, pertolongan pertama, resolusi konflik, keterampilan komunikasi, dan pengalaman kerja. Penulis menemukan pelaku wisata di Desa Poto Tano, Desa Tambak Sari, Desa Kiantar, Desa Senayan dinyatakan belum memenuhi Standar Kompetensi Kerja Nasional Indonesia (SKKNI).